IN-SITU RAMAN SPECTROSCOPY OF QUARTZ: A PRESSURE SENSOR FOR HYDROTHERMAL DIAMOND-ANVIL CELL EXPERIMENTS AT ELEVATED TEMPERATURES - Schmidt C.; Ziemann M.A. (My University, 2000)
Changes in frequency and linewidth of the 206 and 464 cm−1 A1 Raman modes of quartz were determined over temperatures from 23 to 800 °C and simultaneously at pressures ranging between 0.1 MPa and 2.1 GPa using a hydrothermal diamond-anvil cell (HDAC). The frequency shift of the 464 cm−1 peak can be used as a secondary pressure standard for SiO2-saturated systems in HDAC experiments at temperatures up to 560 °C. The frequency of this peak depends quasilinearly on pressure in the studied pressure range. The global slope (∂ν464/∂P)T is 9 ± 0.5 cm−1/GPa. A significant variation of this slope with temperature was not observed. Including literature data, the temperature induced frequency shift of the 464 cm−1 mode is described by (ΔνT)464,P = 0.1 MPa (cm−1) = 2.50136·10−11 ·T4 + 1.46454·10−8·T3 − 1.801·10−5·T2 − 0.01216·T + 0.29 where −196 ≤ T (°C) ≤ 560. The pressure dependence of the linewidth of the 464 cm−1 line increases with temperature. The frequency shifts and linewidths for the 206 cm−1 mode indicate that this line can be used as an alternative to the ruby fluorescence technique as a pressure sensor to about 5 GPa for experiments at room temperature. Both the frequency and linewidth of this mode show significant cross-derivatives (∂2v206/∂P∂T) and (∂2FWHM206/∂P∂T).